ANALYZE DOMINANT FACTORS IN THE IMPLEMENTATION OF VILLAGE FUND POLICY IN KEDIRI REGENCY - Prasetiyo, Prasetiyo; Asmorowati, Sulikah; Mardiyanta, Antun (Natapraja, 2025)
Village funds remain the primary driving force in village development in Kediri, as 44.93% of village revenue in Kediri Regency comes from village funds. However, there are still obstacles in the implementation of the village fund policy in Kediri Regency, which could potentially affect the achievement of policy objectives. In response to this situation, this study aims to analyze the factors influencing the implementation of the village fund policy in Kediri Regency. Referring to Edwards III's Direct and Indirect Impact on Implementation Model and using quantitative methods, it was found that Resources, Attitude, and Bureaucratic Structure have a significant influence on the implementation of village fund policy in Kediri Regency. In contrast, Communication does not have a significant influence. Meanwhile, when the four variables were tested together, the results showed that Communication, Resources, Attitude, and Bureaucratic Structure have a significant influence on the implementation of village fund policy in Kediri Regency, simultaneously. This study recommends that the government prioritise attention to the quality of Standard Operating Procedures, the distribution of roles among implementers, the consistency of implementers' perspectives and attitudes, the quality of human resources, and the provision of adequate authority and facilities.